Initial growth of Swietenia macrophylla seedlings in acidity correction and phosphate nitrogen fertilization - Santos Neto, Julio Conceição dos; Gama, Dráuzio Correia; Oliveira, Everaldo Pereira; Silva, Liniker Fernandes da; Lima, Róbson Borges de (Revista Ecologia e Nutrição Florestal - ENFLO, 2020)
For a commercial reforestation success, it is necessary to know the species specific nutritional requirements used to overcome fertility limitations in a given site, allowing to fertility costs optimize in seedlings production. The objective of this study was to responses evaluate of Swietenia macrophylla King seedlings subject to nitrogen and phosphorus different dosages in corrected soil. The experiment was conducted between January and April 2015 in a greenhouse at the Universidade Federal do Recôncavo da Bahia, in Cruz das Almas (BA). The experimental design was a 5 x 2 factorial scheme (five different doses of phosphorus (Pn) in nitrogen absence and presence [N0 and N1]), making ten treatments, completely randomized. After 90 days of sowing, aerial part height (h) and stem based diameter of seedlings were measured. The data were submitted to variance analysis (ANOVA) at 5% error probability level. Treatments did not statically differ from each other, showing the same effect of P dosages with and without N on soil acidity correction with limestone (CaCO3) condition on initial growth of Swietenia macrophylla seedlings.